Violence against women: a racial perspective (Brazilian Journal of Health Research, 2025)
Introduction: Lethal violence against women in Brazil presents significant racial disparities, disproportionately affecting Black women. This inequality has its roots in a patriarchal and slave-holding historical context, the effects of which continue to structure society and impact the lives of these women. Objective: To analyze the historical and social circumstances influencing the disparity in lethal violence between Black and white women in Brazil, focusing on structural racism and the development of public policies to address violence against women. Methods: A theoretical analysis was conducted based on a literature review and epidemiological data, considering the intersectionality of gender, race, and social context, to understand how structural racism contributes to the vulnerability of Black women. Results: The findings indicate that, despite legislative advances, violence against women persists and disproportionately affects Black women, both in domestic settings and within State institutions. Structural racism and racial stigmatization perpetuate the exclusion of these women, hindering their access to protection policies and justice. Conclusion: It is urgent to formulate intersectional public policies that address racism and gender inequalities, along with the training of professionals for humanized care. Only by recognizing these structural inequalities will it be possible to advance in preventing violence and promoting racial and gender equity.
Keywords: Violence against women; Black population; Racism